Collagen nanofibrous scaffolds for tissue engineering - Piak, Xiang Fu. (2009)
The goal of this project is to research the properties and fabrication process of gelatin and collagen scaffolds. The scaffolds were produced by electrospinning, which is a process that can formulate nanofibers by electrically charging a suspended droplet of polymer melt or solution [1]. The scaffolds were then chemically crosslinked, after which their mechanical properties were tested in their wet states. Different parameters were also used to electrospin the scaffolds, which investigated the effects of varying the concentration of the polymer (gelatin, collagen) and varying the amount of solvent (acetic acid, 2,2,2-trifluoroethanol) used. Two general types of scaffold were investigated in this project. The first type is scaffolds which have nanofibers that are aligned to one another and can be useful for cultivating nerve cells. The other scaffolds are specimens that have nanofibers that are randomly orientated.